A whole-food approach to the in vitro assessment of the antitumor activity of gazpacho. (July 2019) - Campra, Pablo; Aznar-Garcia, Maria Jesus; Ramos-Bueno, Rebeca P.; Gonzalez-Fernandez, Maria Jose; Khaldi, Huda; Garrido-Cardenas, Jose Antonio
Abstract: Gazpacho is a traditional cold soup of the Mediterranean diet consisting of a main base of fresh pureed tomato and other vegetables. Tomato and tomato products have demonstrated chemopreventive activity against several types of cancer through in vitro studies, and in animal and clinical research. Here we have applied a whole-food approach for the preclinical assessment of the antitumor potential of gazpacho . Colon cancer cells (HT-29) were exposed to growing concentrations of gazpacho previously digested in vitro to simulate the delivery of bioactive molecules to colon cells after food consumption. The cytotoxicity of gazpacho ingredients was also tested in independent experiments. Programmed cell death by apoptosis was detected by using a multiparametric analysis that combines image-based bright-field and fluorescence cytometry, intracellular ATP level determination and enzymatic activity of caspase-3/7. Modulation of gene expression of key regulatory genes (p53, Bcl-2, BAX, and cyclin D1) was also investigated. Our cytotoxicity data showed that in vitro digestion of samples allowed the delivery of bioactive levels of antitumor phytochemicals to cultured cells. Controlled experiments showed significant repetitive dose and time-response cytotoxicity of gazpacho . Gazpacho digestates caused net cell death of cultures suggesting synergic activity among phytochemicals from its vegetable ingredients. Multiparametric and genetic analyses showed that gazpacho digestates can trigger colon cancer cells death by apoptosis through the activation of caspase cascade. Our results show that coupled in vitro methodology employed can be applied to investigate the antitumor potential of complex food matrixes or combinations of foods in the diet. Graphical abstract: Unlabelled Image Highlights: Cold tomato soup (gazpacho) digestates reduces colon cancer cells growth in vitro. Tomato combined in gazpacho has increased antitumor activity in vitro against colon cancer cells. The antiproliferative action of gazpacho digestates is mediated by the activation of caspase cascade. Coupled in vitro digestion/cytotoxicity shows a repeatable preclinical antitumor assessment.